2013
DOI: 10.1017/s0272263112000927
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Validity in Eye-Tracking

Abstract: Eye-trackers are becoming increasingly widespread as a tool to investigate second language (L2) acquisition. Unfortunately, clear standards for methodology—including font size, font type, and placement of interest areas—are not yet available. Although many researchers stress the need for ecological validity—that is, the simulation of natural reading conditions—it may not be prudent to use such a design to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 53 publications
0
18
0
1
Order By: Relevance
“…(Winke et al, 2013, p. 207) Most of the articles in the special issue compiled by Winke, Godfroid and Gass, as indeed most SLA eyetracking studies in the past, are interested in a cognitive perspective and deal mainly with experimental studies. Even those concerned with 'ecological validity' (Spinner, Gass, & Behney, 2013) conclude that a more naturalistic setting might have to be sacrificed in favour of unrealistic tasks to gather more reliable and comparable data: they obtained more accurate data by enlarging the font of the text example and changing the layout, resulting in a format that does not compare to students' normal reading material.…”
Section: Illustration 1: Heatmap Of German Teachermentioning
confidence: 99%
“…(Winke et al, 2013, p. 207) Most of the articles in the special issue compiled by Winke, Godfroid and Gass, as indeed most SLA eyetracking studies in the past, are interested in a cognitive perspective and deal mainly with experimental studies. Even those concerned with 'ecological validity' (Spinner, Gass, & Behney, 2013) conclude that a more naturalistic setting might have to be sacrificed in favour of unrealistic tasks to gather more reliable and comparable data: they obtained more accurate data by enlarging the font of the text example and changing the layout, resulting in a format that does not compare to students' normal reading material.…”
Section: Illustration 1: Heatmap Of German Teachermentioning
confidence: 99%
“…He stated that when reading becomes more advanced or conceptually more complex, eye-fixation duration increases and saccade length 4 decreases. Typographical variables in general influence processing, including the quality of print, the length of the line of text, and the amount of space between the letters (Pollatsek, Reichle, & Rayner, 2006;Rayner, 2009;Reichle, Rayner, & Pollatsek, 2003;Reichle, Warren, & McConnell, 2009;Slattery & Rayner, 2010;Spinner, Gass, & Behney, 2013). Fixations are also longer when readers come across long, lowfrequency, or contextually implausible words or phrases (Inhoff, Starr, Solomon, & Placke, 2008;Joseph et al, 2008;Rayner, Warren, Juhasz, & Liversedge, 2004).…”
Section: Eye Tracking and The Use Of Captions For Foreign Language Lementioning
confidence: 99%
“…They found that spacing enhanced the speed of reading while improving the rapid movements of the eye. Spinner, Gass, and Behney (2013) designed two studies to investigate the effect of variety in font size, font type, and display model to determine whether the different ways of presenting the linguistic motive in an eye-tracking experiment would lead to different results. The results of the two studies showed the importance of the display model; in addition, the ideal font size was 24, as used in their second study.…”
Section: Eye Tracking As a Methods Of Studymentioning
confidence: 99%